2015
DOI: 10.1080/10810730.2015.1039678
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance Information-Seeking Behaviors Among the Uninsured

Abstract: As a result of the Affordable Care Act, millions of previously uninsured individuals are facing the daunting task of selecting health insurance. In order to better understand how to reach the uninsured and support their health insurance decision making, this study examined where the uninsured collect information about health insurance and the extent to which they trust those sources and media. We analyzed secondary data on health insurance information-seeking behaviors collected from a survey of 343 uninsured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Our analysis of studies assessing HIL and health care utilization dovetails with other literature assessing the relationship between HIL and navigation of health insurance plan selection and affordability. Studies of factors influencing how people select insurance plans have shown that a lack of cost transparency 33 and a perceived lack of reliable information about how to distinguish different insurance plans 34 are significant barriers towards selecting a plan. One study found that individuals over the age of 50 with concerns about the affordability of health insurance were more likely to delay or avoid care.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of studies assessing HIL and health care utilization dovetails with other literature assessing the relationship between HIL and navigation of health insurance plan selection and affordability. Studies of factors influencing how people select insurance plans have shown that a lack of cost transparency 33 and a perceived lack of reliable information about how to distinguish different insurance plans 34 are significant barriers towards selecting a plan. One study found that individuals over the age of 50 with concerns about the affordability of health insurance were more likely to delay or avoid care.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cancer and survivors make up a high-need population that has often been overlooked in past research on health insurance decision making [37]. To our knowledge, I Can PIC is the first health insurance decision aid designed specifically for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Health Belief Model realistically helps to frame people's behaviors, acknowledging that, at times, just wanting to change one's pattern of payment for healthcare is not enough to make one do so essentially. Furtado et al (24) reveal that illness may lead the uninsured to seek health information, but it might not prompt them to search for insurance information. Two additional elements are incorporated into the HBM to approximate what it takes to move an individual to action.…”
Section: Health Belief Modelmentioning
confidence: 99%
“…Furthermore, Okaro et al (22) argue that implementing NHIS is hinged on both the awareness and perception of sustaining the program in line with its creation objectives. This partially explains why Adebisi et al (23) conclude that NHIS has not fully achieved its goals because health insurance resources delivered via unutilized communication channels that by the target population will likely fail to reach the people they intend to serve (Tichenor et al 1970, cited in (24).…”
Section: Introductionmentioning
confidence: 99%